Culture of marine microalgae, Tetraselmis tetrathele (West) butcher, in annular photobioreactor for application in formation of nanocosmeceuticals - Abd. Wahab, Nurul Farahin (2015)
There has been a remarkable surge of interest on natural products and their application in the cosmeceutical industry. Cosmeceutical are cosmetic-hybrids intended to enhance health and beauty of the skin. Topical delivery of antioxidants from natural marine sources is one of the approaches used to reduce the reverse sign of skin aging. The marine prasinophyte Tetraselmis tetrathele is one of the important microalgae used as feed in aquaculture due to its high nutritional values and able to be mass produced because of its eurythermal and euryhaline characteristics. This indigenous microalga also contains bioactive compounds such as flavonoids, polyphenols and polyunsaturated fatty acids (PUFA), which makes it an appropriate raw material for various product developments in cosmeceutical industries. The antioxidant activity of T. tetrathele (UPMC-A0007) was determined by culturing it in f/2 media for 56 days in 120 L annular photobioreactor. Microalgae biomass was collected six times throughout the culture period to quantify total phenolic (TPC) and antioxidant contents. The antioxidant activities of T. tetrathele’s crude extract were determined by diphenylpicrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) and 2,2'- azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays. Two groups of cell size; small sized-cells (3.0-5.0×10-11 g/cells) and big sized-cells (5.5-8.0×10-11 g/cells) were observed. The total phenolic content of small sized-cell (2.99 ± 0.14 mg GAE/g) was 1.6 times higher compared to big sized-cell. These results suggest that T. tetrathele could be a valuable source of phenolic content and antioxidant. The effective antioxidant production can be achieved by controlling the cell size in during culture process. Identification of phytochemical constituents was achieved by GC-MS analyses. Generally, six main chemical compounds identified were responsible for the bioactivity in both small sized-cells and big sized-cells. Compositions from ternary phase diagrams were selected as pre-formulated emulsions. Topical nanocosmeceutical formulations from palm kernel oil esters (PKOEs) : 1% of crude extract T. tetrathele/Tween 80/water systems were chosen due to the presence of large isotropic liquid region which are suitable for the production of nanoemulsion. Particle size analysis showed that the mean particle sizes of these formulations (T1, T2 and T3) ranged from 102.3 to 249.5 nm. Zeta potential analysis for all emulsions showed negative values from -33.2 to -71.7 mV. Stability studies showed that, after four hours of stirring at room temperature (25°C), the formulations were stable during centrifugation test at 4000 rpm for 15 minutes. In addition, T1, T2 and T3 were stable with no separation at different storage temperatures (4, 25 and 45°C) for the duration of eight weeks. However, between eight to ten weeks, only T1 and T2 were stable at 4, 25, and 45°C. This study illustrated that T1 and T2 formulations are considered to be the most suitable formulation for nanocosmeceutical product because they were stable after undergoing thaw cycles test, storage at room temperature (25°C) and 45°C for more than eight weeks. Moreover, the particle size ranged between 165 to 199 nm which resulted in low occurrence of Ostwald ripening.